2008
DOI: 10.1373/clinchem.2008.105312
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Prolactin and Monomeric Prolactin Reference Intervals Determined by Precipitation with Polyethylene Glycol: Evaluation and Validation on Common ImmunoAssay Platforms

Abstract: Background: Macroprolactin is an important source of immunoassay interference that commonly leads to misdiagnosis and mismanagement of hyperprolactinemic patients. We used the predominant immunoassay platforms for prolactin to assay serum samples treated with polyethylene glycol (PEG) and establish and validate reference intervals for total and monomeric prolactin. Methods: We used the Architect (Abbott), ADVIA Centaur and Immulite (Siemens Diagnostics), Access (Beckman Coulter), Elecsys (Roche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 29 publications
(49 reference statements)
8
119
2
7
Order By: Relevance
“…The monomeric PRL concentration after GFC (GFC monomeric PRL) was calculated according to the formula: (amount of monomeric PRL from GFC (%)/100)!PRL concentration in the native serum obtained by RIA (mg/l). We considered that normal monomeric PRL values obtained from GFC for women were %21 mg/l (%444 mUI/l), as reported by Beltran et al (1).…”
Section: Separation Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The monomeric PRL concentration after GFC (GFC monomeric PRL) was calculated according to the formula: (amount of monomeric PRL from GFC (%)/100)!PRL concentration in the native serum obtained by RIA (mg/l). We considered that normal monomeric PRL values obtained from GFC for women were %21 mg/l (%444 mUI/l), as reported by Beltran et al (1).…”
Section: Separation Methodsmentioning
confidence: 98%
“…Monomeric PRL is generally the most common form circulating in healthy subjects and in hyperprolactinaemic sera (1,2). Macroprolactinaemia (MPRL) is the condition which results when the high molecular mass forms (bPRL, bbPRL) are predominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PEG also induces a partial precipitation of monomeric PRL (up to 25%) so reliance on the relative percentage of recovery lacks specificity which may lead to an underestimated evaluation and misinterpretation of actual PRL levels [24]. This is especially important in cases when an excessive macroprolactin occurs in patient's serum simultaneously with supraphysiological concentrations of monomeric PRL [9,26,29]. Furthermore, it has been reported that the presence of PEG in the sample can interfere with some PRL immunoassay procedures [30].…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, it has been reported that the presence of PEG in the sample can interfere with some PRL immunoassay procedures [30]. To avoid such problems, it has been recommended that each laboratory, undertaking macroprolactin screening, must establish method-specific reference intervals derived by use of PEG-treated sera from healthy individuals [9,26,29]. In routine laboratory diagnostics the post-PEG modified reference range is the best means to accurately identify patients with true hyperprolactinemia [9].…”
Section: Diagnosismentioning
confidence: 99%